Genetics of Type III Bartter Syndrome in Spain, Proposed Diagnostic Algorithm - García Castaño, Alejandro; Pérez de Nanclares, Gustavo; Madariaga, Leire; Aguirre, Mireia; Madrid, Alvaro; Nadal, Inmaculada; Navarro, Mercedes; Lucas, Elena; Fijo, Julia; Espino, Mar; Espitaletta, Zilac; Castaño, Luis; et al. (PloS one, 2013)
The p.Ala204Thr mutation (exon 7) of the CLCNKB gene is a "founder" mutation that causes most of type III Bartter syndrome cases in Spain. We performed genetic analysis of the CLCNKB gene, which encodes for the chloride channel protein ClC-Kb, in a cohort of 26 affected patients from 23 families. The diagnostic algorithm was: first, detection of the p.Ala204Thr mutation; second, detecting large deletions or duplications by Multiplex Ligation-dependent Probe Amplification and Quantitative Multiplex PCR of Short Fluorescent Fragments; and third, sequencing of the coding and flanking regions of the whole CLCNKB gene. In our genetic diagnosis, 20 families presented with the p.Ala204Thr mutation. Of those, 15 patients (15 families) were homozygous (57.7% of overall patients). Another 8 patients (5 families) were compound heterozygous for the founder mutation together with a second one. Thus, 3 patients (2 siblings) presented with the c. -19-?_2053+? del deletion (comprising the entire gene); one patient carried the p.Val170Met mutation (exon 6); and 4 patients (3 siblings) presented with the novel p.Glu442Gly mutation (exon 14). On the other hand, another two patients carried two novel mutations in compound heterozygosis: one presented the p.Ile398_Thr401del mutation (exon 12) associated with the c. -19-?_2053+? del deletion, and the other one carried the c.1756+1G>A splice-site mutation (exon 16) as well as the already described p.Ala210Val change (exon 7). One case turned out to be negative in our genetic screening. In addition, 51 relatives were found to be heterozygous carriers of the described CLCNKB mutations. In conclusion, different mutations cause type III Bartter syndrome in Spain. The high prevalence of the p.Ala204Thr in Spanish families thus justifies an initial screen for this mutation. However, should it not be detected further investigation of the CLCNKB gene is warranted in clinically diagnosed families.